2019
DOI: 10.1111/trf.15177
|View full text |Cite
|
Sign up to set email alerts
|

The use of cryopreserved platelets in the treatment of polytraumatic patients and patients with massive bleeding

Abstract: BACKGROUND The short shelf‐life of fresh platelets limits their efficient inventory management and availability during a massive transfusion protocol. Risk of insufficient availability can be mitigated by building an inventory of cryopreserved platelets (CPs). METHODS A comparative study of fresh apheresis platelets (FAPs) and CPs was performed. Type‐O CPs were processed with DMSO frozen at −80°C and reconstituted in thawed AB plasma. All patients enrolled in the study had the following parameters evaluated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…There were no thrombotic events related to cryopreserved PLTs and no differences in adverse event rates found between cohorts. These safety results are largely consistent with those reported for previous trials …”
supporting
confidence: 92%
See 1 more Smart Citation
“…There were no thrombotic events related to cryopreserved PLTs and no differences in adverse event rates found between cohorts. These safety results are largely consistent with those reported for previous trials …”
supporting
confidence: 92%
“…No serious adverse events were observed, and the cryopreserved PLT transfusions appeared to be effective for bleeding patients with thrombocytopenia. A second trial run in the Czech Republic by Bohonek and colleagues found that transfusing cryopreserved PLTs or standard apheresis PLTs were associated with similar clinical outcomes in trauma patients and patients with massive bleeding.…”
mentioning
confidence: 99%
“…There has been a resurgence in interest in cryopreservation of platelets over the past decade . Although CPPs have been transfused for prophylactic purposes, the most prevalent indication for CPPs has been the treatment of active bleeding . In the future, CPPs could represent one component in a multiproduct inventory where the choice of product is dictated by individual patient requirements.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although CPPs have been transfused for prophylactic purposes, 2,13,14 the most prevalent indication for CPPs has been the treatment of active bleeding. [15][16][17][18][19] In the future, CPPs could represent one component in a multiproduct inventory where the choice of product is dictated by individual patient requirements. RTstored platelets would likely remain the product of choice for prophylactic transfusions, while CPPs may be reserved for actively bleeding patients, particularly in locations where an RT inventory is not available, such as remote or military environments.…”
Section: Discussionmentioning
confidence: 99%
“…A Phase I human study found lower 24‐hour PLT recovery in comparison to liquid‐stored PLTs, but with survival times exceeding US Food and Drug Administration requirements and with no associated adverse events . Three small Phase II trials have been performed in bleeding hematology, cardiac surgery, and a mixed population of mostly trauma patients, all of which suggested at least comparable hemostatic efficacy and no evidence of adverse effects. However, the total number of patients transfused cryopreserved PLTs in these three trials was only 73.…”
mentioning
confidence: 99%